2015
DOI: 10.1158/0008-5472.can-14-3363
|View full text |Cite
|
Sign up to set email alerts
|

ΔNp63α Promotes Breast Cancer Cell Motility through the Selective Activation of Components of the Epithelial-to-Mesenchymal Transition Program

Abstract: Cell identity signals influence the invasive capability of tumor cells, as demonstrated by the selection for programs of epithelial-to-mesenchymal transition (EMT) during malignant progression. Breast cancer cells retain canonical epithelial traits and invade collectively as cohesive groups of cells, but the signaling pathways critical to their invasive capabilities are still incompletely understood. Here we report that the transcription factor ΔNp63α drives the migration of basal-like breast cancer (BLBC) cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
130
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(149 citation statements)
references
References 53 publications
19
130
0
Order By: Relevance
“…p63 has also been implicated in regulating epithelial-mesenchymal transition (EMT) [38][39][40], although this is a partial effect in which ΔNp63 both promotes and inhibits different components of EMT through induction of Slug and simultaneous inhibition of ZEB1/2 [39,40]. Compatible with a partial effect of p63 on phenotypic reprogramming, we found that p63 loss causes incomplete transition from basal-type to luminal-type epithelial cells; lack of p63 in these basal cancer cells did not induce estrogen receptor and did not decrease CK5 levels.…”
Section: Discussionmentioning
confidence: 99%
“…p63 has also been implicated in regulating epithelial-mesenchymal transition (EMT) [38][39][40], although this is a partial effect in which ΔNp63 both promotes and inhibits different components of EMT through induction of Slug and simultaneous inhibition of ZEB1/2 [39,40]. Compatible with a partial effect of p63 on phenotypic reprogramming, we found that p63 loss causes incomplete transition from basal-type to luminal-type epithelial cells; lack of p63 in these basal cancer cells did not induce estrogen receptor and did not decrease CK5 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous mathematical models and experimental studies have identified multiple phenotypic stability factors (PSF) that can stabilize a hybrid E/M phenotype such as OVOL1/2 [63][64][65], GRHL2 [66], ∆NP63α [67], and NUMB/NUMBL [68] and facilitate collective cell migration. GRLH2 and OVOL1/2 directly target the miR-200-ZEB axis regulating EMT [63,66], while NUMB/NUMBL modulates EMT via Notch-Jagged signaling [68].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms enabling cancer cells to maintain hybrid E/M phenotype(s), however, remain largely unclear. Recent experimental and computational studies have suggested that a set of 'phenotypic stability factors' (PSFs) such as GRHL2, OVOL2, ΔNp63α and NUMB can help cells in maintaining a hybrid E/M phenotype by preventing 'cells that have gained partial plasticity' from undergoing a full EMT [5][6][7][8][9][10] and thus enabling collective cell migration. Knockdown of these PSFs drove the cells to a complete EMT in vitro and in vivo, while their exogenous overexpression can drive Mesenchymal-Epithelial Transition (MET) -the reverse of EMT [11].…”
Section: Introductionmentioning
confidence: 99%